Enhancing the Performance of Concrete Coupled Shearwall Using Shape Memory Alloys - Hamidreza Nasiri; Mehdi Ghassemieh (Engineering Reports)
ABSTRACT Utilizing self‐centering materials, such as shape memory alloys (SMA), as reinforcement in concrete structures can positively influence their performance during and after earthquakes. Despite the high cost of SMAs, their unique flag‐shaped stress–strain behavior and effective energy dissipation make them an attractive material choice in some structures. This study evaluates the application of iron‐based SMAs in enhancing the seismic performance of coupled concrete shear walls. The purpose is to identify optimal SMA placement strategies within the walls' plastic hinges to improve energy dissipation, reduce residual drift, and enhance ductility. This research explores pre‐tensioned and non‐pre‐tensioned SMA configurations through macro‐element modeling and cyclic analysis. Presenting a comparative framework that balances material efficiency and structural performance differentiates this study from prior studies focused predominantly on SMA benefits in isolated structural applications. Two optimization scenarios are proposed: maximizing energy dissipation and minimizing residual drift, and reducing SMA usage while maintaining structural efficiency. The results indicate that pre‐tensioned SMAs in the wall web provide the most significant improvement in seismic behavior, significantly reducing residual drift and increasing ductility. This approach offers a cost‐effective solution for improving earthquake resilience in structures.